CORAK ESTETIKA PERTUNJUKAN WAYANG GAGRAG BANYUMAS SAJIAN PANDU NUR PRASTIYO LAKON SEMAR BANGUN KAYANGAN - salim (Akademi Seni dan Desain Indonesia Surakarta, 2025)
This research focuses on the study of popular aesthetics in the Banyumasan style shadow puppet performance presented by Pandu Nur Prastiyo through the play Semar Bangun Khayangan. The formulation of the problems raised in this research include: (1) What is the structure of the Banyumasan style shadow puppet performance presented by Pandu Nur Prastiyo in the play Semar Bangun Kayangan? (2) What is the form or aesthetic pattern displayed in the 1 Vol. 11 | No. 1 | Tahun 2025 performance?